A 16-channel OCDMA system (4 OCDM /spl times/ 4 WDM) based on 16-chip, 20 Gchip/s superstructure fibre Bragg gratings and DFB fibre laser transmitters - Teh, P.C.; Ibsen, M.; Fu, L.B.; Lee, J.H.; Yusoff, Z.; Richardson, D.J. (Optical Fiber Communications Conference: Post Conference Digest, 2002)
In conclusion, we have experimentally demonstrated that the SSFBGs coding/decoding approach can be implemented using practical all-fibre sources in a 16-channel OCDMA/WDM system. A complete evaluation of the BER performance of all the 16 channels in the system is obtained. The experiments also demonstrated that error free performance can be obtained for a distance of 50 km of transmission without any complicated dispersion compensation or some means of nonlinear filtering at the receiver. These results highlight that the SSFBG approach provides an extremely powerful and flexible way of performing many of the elementary optical processing functions required within both OCDMA and packet-switched networks.